Business Models for Frugal Innovation in Emerging Markets: The Case of the Medical Device and Laboratory Equipment Industry. (August 2017) - Winterhalter, Stephan; Zeschky, Marco B.; Neumann, Lukas; Gassmann, Oliver
Abstract: This study investigates business models for frugal innovation (i.e. a specific form of resource-constrained innovation) in the medical device and laboratory equipment industry in the context of emerging markets. Based on original data from five case studies, we investigate how firms can set up value creation and value capturing mechanisms to reach new customer segments in remote rural areas with unprecedented value propositions. With this research, we contribute to the literature on frugal innovation and business models in emerging markets. It is among the first empirical studies to apply a fine-grained perspective on resource-constrained innovation in emerging markets. In doing so, we focus on its most disruptive form, which is when these innovations entail entirely new applications. We advance and detail the value proposition for frugal innovation in these industries and argue that frugal innovation create new markets. Further, we show how firms set up their value creation and value capturing mechanisms to achieve the value proposition and identify two distinct Research & Development (R&D) strategies for frugal innovation. Highlights: Frugal innovations enable new, unprecedented applications. There is a threefold value proposition in frugal innovations in the healthcare industry. Firms need to tailor value creation and capturing mechanisms to implement frugal business models. There are two specific R&D strategies for the development of frugal business models.